Modern Management Influencing Sustainable Organization Development & Strategic Management - Nikhilesh Nawani, Dr. Sana Zaidi; Dr. Pallavi Bhardwaj, Dr. Devkanya Gupta (Journal of Informatics Education and Research, 2025)
In the contemporary business environment, modern management practices are central to achieving sustainable organizational development and strengthening strategic management. This paper explores how digital transformation, agile leadership, corporate social responsibility (CSR), environmental–social–governance (ESG) integration, and green innovation influence sustainability outcomes in organizations. Drawing on global trends and Indian corporate data such as the ₹25,932 crore CSR expenditure in FY 2022–23 and the growing role of SEBI’s Business Responsibility and Sustainability Reporting (BRSR) the study highlights that sustainability is no longer a compliance exercise but a strategic imperative. Empirical evidence demonstrates that firms embedding sustainability in strategy achieve higher financial performance, brand loyalty, and long-term resilience. Case examples from Tata, Infosys, and Reliance illustrate the role of strategic management in aligning with the United Nations Sustainable Development Goals (SDGs). The findings conclude that modern management fosters a triple advantage of profitability, social legitimacy, and environmental stewardship.